Enhancing science students’ participation in writing argumentative essays in Biology class through a genre-based approach (an action research) - Daniel Frengki Kamengko; Ifoni Ludji; Irna A. Neolaka (Prodi Pendidikan Biologi FKIP Universitas Kristen Artha Wacana, 2021)
ABSTRAK Metode genre based telah dipakai dalam banyak studi. Metode ini juga memberikan banyak kontribusi terhadap peningkatan mutu penulisan dalam berbagai konteks pelajaran. Tujuan dari penelitian ini adalah untuk meningkatkan partisipasi siswa kelas IPA dalam menulis teks argumentasi pada pelajaran biologi dengan menggunakan metode genre based di SMAN 1 Kupang Timur. Penelitian ini menggunakan metode penelitan tindakan kelas yang terdiri dari dua fase. 41 siswa kelas IPA pada SMAN 1 Kupang Timur terlibat dalam penelitian ini. Metode genre based ini diaplikasikan selama empat kali pelatihan selama satu bulan berfokus pada bagaimana siswa menulis teks argumentasi dalam pelajaran biologi. Teks argumentasi siswa dinilai dengan menggunakan penilaian “systemic functional grammar” dalam pemberian pre-test dan postest. Hasil penelitian menunjukan bahwa metode genre based meningkatkan partisipasi dan nilai menulis siswa kelas IPA. Kata Kunci: pendekatan genre-based, teks argumenatsi, penelitian tindakan, systemic functional grammar ABSTRACT Genre-based approach has been used frequently in many studies. It has been shown in any number of studies to contribute to the development of writing across different contexts. The main purpose of the research was to increase science students’ participation in argumentative essay writing using a genre-based approach at SMAN 1 Kupang Timur. This study applied an action research method which was comprised of two cycles. 41 students at SMAN 1 Kupang Timur participated in the study. A genre-based approach was applied four times over the course of a month to teach the students how to write argumentative essays. Students’ argumentative essays were measured by the systemic functional grammar framework in pretest and post-test. The research findings indicated that the genre-based approach increased students’ participation and scores in argumentative writing. Key words: genre-based approach, argumentative texts, action research, systemic functional grammar